Using design thinking to engage autistic students in participatory design of an online toolkit to help with transition into higher education. Issue 2 (20th June 2016) - Fabri, Marc; Andrews, Phoenix C.S.; Pukki, Heta K.
Abstract : Purpose: – The purpose of this paper is to reflect on engaging young autistic people in the participatory design of the Autism & Uni online toolkit. The purpose of the toolkit is to provide autistic students with information and strategies for dealing with the challenges they may encounter when entering higher education. The study adds to existing research on participatory design by considering the specific needs and contributions of autistic people who are of average or higher intelligence, academically competent and generally articulate, a group that has received limited attention hitherto. Design/methodology/approach: – The research used a five-step design thinking approach and engaged multiple stakeholders at different points. The paper covers the whole process, paying particular attention to the final two steps of prototyping and testing. During three participatory design workshops, autistic people acted as co-designers and co-creators. Findings: – The workshops were effective in engaging participants in various design activities and rich discussions. Several assumptions about capabilities and preferences of autistic people were challenged. Design thinking proved a suitable framework for involving this group in the creation of solutions that serve their needs. Research limitations/implications: – Because of the low number of workshop participants (11), research results may lack generalisability. Also, the workshop format with its focus on group activities may discourage some autistic people to take part. Further work is needed to explore this and to confirm the reported findings. Practical implications: – The paper offers practical advice regarding how to involve autistic people in co-design activities. Social implications: – The research contributes to a strength-based view of autism, rather than one that focuses on deficits. Originality/value: – The paper provides new perspectives on the strengths of autistic people in participatory design settings, with a focus on those autistic people who are of average or higher intelligence and able to communicate effectively.